(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to investigate the clinical epidemiological characteristics and identify factors associated with the recurrence frequency of pneumonia in children. Methods: A cross-sectional descriptive study was conducted on 150 children diagnosed with recurrent pneumonia from October 2023 to September 2024 at the Outpatient and Voluntary Treatment Department of Nghe An Obstetrics and Pediatrics Hospital. The study analyzed the relationship between various factors and the recurrence frequency of pneumonia. Results: The prevalence of recurrent pneumonia was 8.0%. The majority of cases were in children aged 2–12 months, accounting for 44.7%. The incidence was higher in males than females, with a male-to-female ratio of 1.78. The most common recurrence frequency was three episodes (34.7%), with an average of 3.13 ± 1.21 episodes. The etiological agents identified in recurrent pneumonia episodes included Haemophilus influenzae (6.0%), Streptococcus pneumoniae (10.0%), Mycoplasma pneumoniae (4.0%), RSV virus (11.0%), influenza virus (3.0%), while 66.0% of cases had no identifiable causative pathogen. Recurrent pneumonia occurring more than four times was significantly associated with a history of personal allergies (p<0.05, OR 7.57, 95% CI [0.95–15.12]) and exposure to cigarette smoke or daycare attendance (p<0.05, OR 7.3, 95% CI [2.68–20.02] and OR 3.57, 95% CI [1.57–8.14], respectively). Conclusion: The prevalence of recurrent pneumonia was 8.0%, with an average recurrence of 3.13 ± 1.21 episodes. A causative pathogen was identified in 44.0% of cases. Risk factors associated with more than four recurrence episodes included daycare attendance, exposure to cigarette smoke, and a personal history of allergic conditions.